Kinetic Theory of Nonequilibrium Ensembles, Irreversible Thermodynamics, and Generalized Hydrodynamics. Nonrelativistic Theories / Volume 1, ([2016]) - Eu, B. C (Byung Chan), 1935-
No abstract available